Enhanced activity of Ru/TiO2 catalyst using bisupport, bentonite-TiO2 for hydrogenolysis of glycerol in aqueous media - Noraini Hamzah; Norasikin Mohamad Nordin; Ainol Hayah Ahmad Nadzri; Yah Awg Nik; Mohamad Kassim; Mohd Ambar Yarmo (Elsevier, 2012)
A combination of bentonite-TiO2 was used as support to enhance the activity of Ru/TiO2 catalyst in hydrogenolysis of aqueous glycerol to 1,2-propanediol. A series of bentonite, TiO2, SiO2 and Al2O3 supported Ru catalyst were fabricated and characterized by XRD, XPS, BET, FESEM-EDX and TEM to establish some physicochemical properties of the catalysts. The activity of the catalysts was tested in glycerol hydrogenolysis reaction and were found to be in the following increasing order: Ru/SiO2 < Ru/TiO2 ≈ Ru/Al2O3 < Ru/bentonite. In particular, Ru/bentonite catalyst recorded the highest conversion (62.8%) of glycerol (20 wt%) with 80.1% selectivity to 1,2-pronediol at 150 ◦C, 20–30 bar H2 with a reaction duration of 7 h. The Ru/TiO2 catalyst exhibited the highest selectivity (83.7%) for hydrogenolysis of glycerol to 1,2-propanediol and with 38.8% conversion only. The activity of Ru/TiO2 catalyst was enhanced by adding bentonite to the titania support at 1:2 ratio resulting in an 80% increasing the activity from 38.8% to 69.8% under the same optimum condition for Ru/TiO2 while maintaining an 80% selectivity to 1,2-propanediol. TPD-NH3 analysis found that mixed support could increase catalyst acidity. CO pulse chemisorption analysis revealed that Ru particles was well dispersed with the smallest average size particles (1.5 nm) which could contribute to high activity of Ru/TiO2 catalyst for hydrogenolysis of glycerol